2013
DOI: 10.1111/efp.12024
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora dieback on narrow leaved ash in the Black Sea region of Turkey

Abstract: Summary Severe dieback symptoms were observed in a 490‐ha moist ash (Fraxinus angustifolia) lowland forest stand, comprising trees over 100 years old and in 100 ha of newly planted F. angustifolia near Sinop, in Turkey. Five of the 10 soil samples collected around stem bases of the diseased trees were baited using ash leaves and yielded a Phytophthora sp. This heterothallic species produced non‐caducous, non‐papillate sporangia in non‐sterile soil extract, and fluffy, even growth on corn meal and potato dextro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…plurivora from clade 2 is known to be a serious pathogen of many forest trees, including oak, beech, and Alnus glutinosa seedlings. This species can cause dieback and root loss and is most frequently associated with cankers in Europe, North America, and Asia [31][32][33][50][51][52][53][54][55]. Via the examination of plant tissues and soil samples, it has been reported to cause cankers in wild apple forests in Xinjiang [17], corroborating its discovery in stream water and soil samples in the present study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…plurivora from clade 2 is known to be a serious pathogen of many forest trees, including oak, beech, and Alnus glutinosa seedlings. This species can cause dieback and root loss and is most frequently associated with cankers in Europe, North America, and Asia [31][32][33][50][51][52][53][54][55]. Via the examination of plant tissues and soil samples, it has been reported to cause cankers in wild apple forests in Xinjiang [17], corroborating its discovery in stream water and soil samples in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…P. lacustris, which like P. gonapodyides belongs to clade 6, is widely distributed globally. Initially identified as a saprotroph that infects plant detritus, it has now been shown to cause significant damage to fine roots and weak-to-moderate bark lesions in Alnus glutinosa and Prunus persica in Portugal, Italy, and Turkey, among other places [33][34][35][36][37]. Samples in previous research on this species were from soil, trees, and roots, while in the present study, they were mostly taken from streams, with a few collected by canopy drip and from the soil by baiting.…”
Section: Discussionmentioning
confidence: 99%
“…Ash dieback is a serious problem affecting most European countries and one of the main goals in management strategies is to determine all the contributing factors of ash dieback in Europe. In addition to infections by H. fraxineus as a main cause of ash dieback, other factors may possibly play role in this phenomenon, including infection with Phytophthora species (Orlikowski et al 2011;Akilli et al 2013) and Armillaria species (Skovsgaard et al 2010;Enderle et al 2013). Results showed high aggressiveness of H. fraxineus to young ash plants, with indications that root infections with Phytophthora spp.…”
Section: Discussionmentioning
confidence: 98%
“…soils and necrotic tissues associated with severe damage of significant forest tree species (Brasier et al 2005;Jung et al 2013), including ash (Orlikowski et al 2011;Akilli et al 2013). Tkaczyk et al (2016) also reported isolation of several different Phytophthora species from ash in Białowieża Forest Nature Reserve in Poland.…”
mentioning
confidence: 95%
“…Since the first report, P. lacustris, P. plurivora and two other species (P. megasperma and P. sp. hungarica) were isolated respectively from symptomatic Fraxinus angustifolia in Turkey and symptomatic F. excelsior in Poland and Germany (Akilli et al 2013;Langer 2017;Pacia et al 2017). The affected trees showed reduction of fine roots, along with collar rot, dark-brown necrosis paths in the inner bark close to the stem base, aerial canker and dark tally spot in the bark .…”
Section: Root and Collar Rot (Phytophthora Spp)mentioning
confidence: 99%